Study the phases equilibrium of the binary system MnO2- Co3O4 - Saleh, Rasha Hosam; Deeb, Mohammad Ali (Journal of natural sciences, life and applied sciences, 2022)
Samples were prepared within the MnO2- Co3O4 binary system at different molar percentages de- pending on the ceramic method using amorphous manganese dioxide MnO2, and crystalline cobalt oxide Co3O4, according to (x)MnO2- (100- x) Co3O4, for the molar percentages (x= 5, 10, 25, 40, 60, 75, 80), Then they were prepared in tablets form using a manual hydraulic press. The heating process was carried out under a specific heat program, and the samples were heated at 150°C for 8 hours. The grinding and pressing operations were repeated by the same mechanism, with an increase in temperature of 25°C each time until reaching 550oC. After that the samples were sintered at 550oC for 15 hours. The prepared samples were studied using X- rays diffraction device (XRD), and a melting point determination device mp.cwf 1200. The resulting spectra of the samples were compared with the spectra of the raw materials used, and their parameters. Where the results showed a formation of a crystalline solid solution on the basis of cobalt oxide compound up to the molar percentage of 40MnO2- 60Co3O4 mole%, and a formation of a new crystalline compound with the chemical formula Co6Mn3O14 at the molar percentage of 60MnO2- 40Co3O4 mole%, and a formation of a crystalline solid solution on the basis of the new crystalline compound Co6Mn3O14 which starts at the molar percentage 75MnO2- 25Co3O4 mole%. The melting temperatures of the samples were determined, then the phase diagram of the studied system was drawn. Based on these results, it is useful to apply the samples that were prepared and resulted in different crystalline compounds and solid crystal phases in batteries and capacitors, in order to develop them and increase their capacity, especially that the highest temperature used is 550oC, and within simple preparation conditions, which increases the possibility of its application easily.